Development of Post-Occupancy Design Evaluation TM (PODE) technique as a design studio criteria for future Open-Plan System (OPS) - Suaimi., Nursyuhada; Dolah., Mohd Shahrizal; Raja Ahmad Effendi., Raja Ahmad Azmeer; Ramly, Saiful Hasley; Bolong, Jusang (RSIS International, 2024)
This study aims to identify the standard guidance priority of design criteria for open-plan system design furniture for students. The main data collection was conducted at UPM involving design students who occupied the studio space. This study has adopted a mixed-method approach through the close-ended interview for the Designer Voice (DV) and Participatory Design (PD) for the User Voice (UV). The DV and UV were transferred into the Design Evaluation (DE) survey form. They were used to identify the priority of design criteria of the Open-plan System (OPS) furniture for student use. The ranking system in DE analysis will be used to develop the Post- Occupancy Design EvaluationTM (PODE) form. The PODETM form is a novel approach that adopts the concept of the Post-Occupancy Evaluation (POE) and Quality Function Deployment (QFD) as design approach references. The result revealed that the priority of design criteria led to the usability while sketching, ergonomics of the table, aesthetic in color, and function in flexibility. The result also revealed the user requirement to change the height and angle of a table for sketching are the highest prior criteria in standard guidance of OPS furniture students use.